2016
DOI: 10.4314/ajcem.v17i3.1
|View full text |Cite
|
Sign up to set email alerts
|

Association of <i>sul</i> genes and class 1 integron with trimethoprimsulfamethoxazole Resistance in <i>Stenotrophomonas maltophilia</i> clinical isolates in Zagazig University, Egypt

Abstract: Background: Stenotrophomonas maltophilia (S.maltophilia) is an intrinsically drug resistant opportunistic pathogen associated with serious infections in humans. Acquired resistance to trimethoprim-sulfamethoxazole (SXT,co-trimoxazole), the main stay of therapy against S. maltophilia ,has made its treatment more problematic. Objectives: This work aimed to determine the occurrence of SXT resistance among S. maltophilia isolated from Zagazig University Hospitals in Egypt and to assess the association of sul genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 4 publications
(6 reference statements)
1
0
0
Order By: Relevance
“…In the current study, the presence of dfrA13 was reported in clinical isolates of S. maltophilia for the first time in Iran, and the frequency of this gene was 5.32%. Similar to other studies, sul3 was not detected in clinical isolates of S. maltophilia [ 44 , 45 ]. This newest sulfonamide-resistance gene is usually located on plasmid and especially isolated in nonclinical specimens including water, soil, sewage loving animals, and animal farm [ 18 ].…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, the presence of dfrA13 was reported in clinical isolates of S. maltophilia for the first time in Iran, and the frequency of this gene was 5.32%. Similar to other studies, sul3 was not detected in clinical isolates of S. maltophilia [ 44 , 45 ]. This newest sulfonamide-resistance gene is usually located on plasmid and especially isolated in nonclinical specimens including water, soil, sewage loving animals, and animal farm [ 18 ].…”
Section: Discussionsupporting
confidence: 90%